Examination of ELT Lecturers’ Digital Technology Integration Levels Via SAMR Model During Emergency Remote Education - Orak, Suheyla Demirkol; Alagozlu, Nuray (My University, 2025)
It is undeniable that humanity depends heavily on the effective application of technology in today’s globalised and competitive world, and the field of language education is strongly impacted by the era of digitalisation, which facilitates interactive and transformative teaching environments on various language teaching platforms. Moreover, it is necessary to combat various pandemics and devastating natural disasters through technological advancements without falling behind the 21st century. The current century demands a higher level of awareness and practicality regarding technology facilitation, apart from higher-order skills. Considering this cognitive approach and awareness, the present study investigated the digital technology integration levels of the English Language Teaching lecturers during the COVID-19 pandemic emergency remote education conditions using Substitution, Augmentation, Modification, Redefinition (SAMR) Model. A correlational design was employed through the administration of a Likert-type questionnaire to 243 English Language Teaching lecturers at 20 universities geographically dispersed into the seven districts of Turkey. The universities were selected based on the statistical data of the Nomenclature of Territorial Units for Statistics. The results indicated that synchronous teaching platforms were mainly utilised as overhead projectors, revealing the dominant usage of Substitution level without the lecturers’ effective interferences in the activities. Transforming either the frame or content of the original materials was also largely promoted under the Modification level, but it was placed after the Redefinition level, which is time and effort- demanding, and promoted more extensively after the Substitution level. The Augmentation level was the least promoted one, since the participants considered that increasing or decreasing the number of robotic activities is less useful than Modification and Redefinition level-appropriate practices. Furthermore, correlations were found between the participant lecturers’ digital technology integration levels and their gender, background education and online teaching experiences, whereas seniority and age were not significant indicators of the participants’ digital technology integration levels.
Keywords: Emergency remote education; digital technology integration; SAMR model